THE EFFECT OF ADDITION OF INDIAN COPPERLEAF FLOUR AND TAOGE FLOUR COMBINATION IN ARTIFICIAL FEED ON FEED UTILIZATION EFFICIENCY AND GROWTH OF TILAPIA (OREOCHROMIS NILOTICUS) - Hernowo, Ilham Agung; Pinandoyo, Pinandoyo; Hutabarat, Johannes; Herawati, Vivi Endar (Indonesian Aquaculture Society (MAI), 2020)
Tilapia is a superior freshwater commodity in Indonesia. The problem with tilapia farmers is the high price of commercial feed because raw materials are still imported. Alternative materials are needed to reduce the cost of feed. One of the treatments is by substituting local raw materials that can stimulate the growth of tilapia, namely by substituting a combination of earrings spinach flour and bean sprouts in the artificial feed that is useful to spur the growth of cultivated tilapia. This study aims to determine the best dose substitution and effect of earrings spinach flour and waste sprouts flour on artificial feed to the efficiency of feed utilization and growth of tilapia fish (Oreochromis niloticus). The method used is an experimental method with a Completely Randomized Design (CRD) with 4 treatments and 3 repetitions. Test fish used was tilapia with an average weight of 3.37 ± 0.16 grams which were kept in a bucket of 15 L. water. The combination of earrings amaranth flour and bean sprouts flour used was in the ratio of 0%: 0% (A), 100 %: 0% (B), 50%: 50% (C) and 0%: 100% (D). Observation variables included the efficiency of feed utilization, growth, life pass, and water quality. The best results of this study were 50%: 50% (C) with, RGR, EPP, FCR, PER, TKP and Survival, respectively, 76.60 ± 3.07% / day, 76.60 ± 3 , 07%, 1.31 ± 0.05, 2.25 ± 0.04% 91.37 ± 1.45 grams and 86.67 ± 6.67a%. Water quality results in maintenance in the optimal range.